PERSEPSI PERAWAT TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE DI IGD RUMAH SAKIT PUSAT PERTAMINA - Kanyia Salsabilla, (2023)
Services in the Emergency Department (IGD) require fast and precise handling in providing health care to patients. The condition of patients who come to the emergency room has a variety of levels of severity and cannot be predicted as a result of these conditions is likely to cause errors in the process of triage, assessment, diagnosis, management, and evaluation. Artificial Intelligence is a solution in reducing waiting time and errors in diagnosing. The purpose of this study was to determine nurses' perceptions of the use of Artificial Intelligence (AI) in health services at the Emergency Room of Pertamina Central Hospital. This study used a quantitative observational research design with a descriptive approach. The sample size was 28 emergency room nurses at Pertamina Central Hospital according to the inclusion and exclusion criteria. The sampling technique used total sampling. The research instrument used a Health Worker Perception of Artificial Intelligence questionnaire and a questionnaire using Google Forms. The results of this study indicate that the level of perception of nurses in the emergency room of Pertamina Central Hospital is in the medium perception category.